Discovering entrepreneurial strategies : impact of strategic mechanisms in entrepreneurial decision makings on innovation performance of resource-constrained firms - Kim, Jinyoung (2018)
In this dissertation, I explore entrepreneurial decision making processes to discover entrepreneurial strategies and study the impacts of these strategies on innovation performance of resource-constrained firms. The first essay tells the stories and subsequent analyses of 37 university spin-off technology start-ups in the United States to identify a set of strategic mechanisms that the start-ups adopt in order to move forward the tumultuous initial stage of technology commercialization. Longitudinal multiple cases study method is used to isolate a series of pattems in entrepreneurial decision makings, especially regarding strategic decisions that involve major changes in start-up goals, and to analyze commonalities and idiosyncrasies among these pattems between successfully progressing start-ups and unsuccessful ones. The start-ups that move forward successfully are found to be the ones that iteratively transform their goals using three strategic mechanisms of resource search and recombination, options generation, and contingency exploitation. Based on the strategic mechanisms identified in the first essay, the second essay reports the impact of these strategic mechanisms as well as start-up entrepreneurs' innovative behavioral and cognitive skills on innovation performance of 153 start-ups in Singapore by using survey questionnaire and face-to-face interview. A set of survey questionnaire is developed for options generation and contingency exploitation strategies based on the real options theory, effectuation theory, and strategic reactiveness. The findings of this study (1) confirm that the strategic mechanisms identified in the first essay are indeed positively associated with more innovativeness of start-ups' new products or services, (2) empirically show that the options generation strategy and contingency exploitation strategy are used concurrently as the two gears of innovation to leverage uncertainty in a flexible, yet pre-planned way, and (3) elaborate on how certain innovative skills of entrepreneurs facilitate the identified strategic mechanisms.